Aggressiveness, Mating Behaviour and Lifespan of Group Housed Rabbit Does - Zsolt Gerencsér; Zsolt Matics; Rubina T. Szabó; Károly Kustos; Annamária Mikó; István Nagy; Meinrad Odermatt; Tamás Atkári; Zsolt Szendrő (Animals, 2019)
Aggressiveness is one of the main problems in group housing of rabbit does. The aim of the experiment was to investigate the frequency of aggressiveness and mating behaviour as well as the lifespan of does depending on group composition. The female and male rabbits were housed in one of the 7.7 m2 pens (four females and one male per pen). Based on the ages of female rabbits two homogenous groups (HOM) were formed containing four 17-week-old females and two heterogeneous groups (HET) containing three 17-week-old and one 1-year-old female. Twenty-four-hour video recordings were taken during the first month after assembling the groups, and the aggressive actions (fights) and matings were counted. The lifespan was examined over a 200-day experimental period. On the day after assembling the groups the number of fights among does was high in HET group. The same aggressive behaviour only started a week later in HOM group, and some fights between females and the male were also observed. The daily peaks of aggressiveness were in the morning (after the light on) and in the evening (before and after the lights off). The primary position of females in the hierarchy was clear but sometimes no differences were detected among the subordinate females. The mortality of does was connected with their rank order. The number of matings was very high on the day of assembling the groups and a second small peak was observed at the end of the hypothetical pseudo-pregnancy. In addition to mating between male and females, female−female and female−male mounting was also observed. Despite of the small sample size it seems that aggressive behaviour is frequent in group housing systems, which is contrary to animal welfare. Natural mating is not effective in group-housing system.